2004
DOI: 10.1109/tnsre.2004.834627
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of EEG activity into cursor movement by a brain-computer interface (BCI)

Abstract: The Wadsworth electroencephalogram (EEG)-based brain-computer interface (BCI) uses amplitude in mu or beta frequency bands over sensorimotor cortex to control cursor movement. Trained users can move the cursor in one or two dimensions. The primary goal of this research is to provide a new communication and control option for people with severe motor disabilities. Currently, cursor movements in each dimension are determined 10 times/s by an empirically derived linear function of one or two EEG features (i.e., s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
112
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(122 citation statements)
references
References 19 publications
0
112
0
3
Order By: Relevance
“…brain-machine interface | motor learning | plasticity | electrophysiology | high gamma O ver the last 50 years, it has been demonstrated that, when given feedback, the brain can learn to volitionally modulate the activity of single neurons (1)(2)(3)(4)(5) and populations of neurons (6)(7)(8)(9). This modulation can occur in the absence of overt movement (6,9) or even when overt movement is not possible (3,10).…”
mentioning
confidence: 99%
“…brain-machine interface | motor learning | plasticity | electrophysiology | high gamma O ver the last 50 years, it has been demonstrated that, when given feedback, the brain can learn to volitionally modulate the activity of single neurons (1)(2)(3)(4)(5) and populations of neurons (6)(7)(8)(9). This modulation can occur in the absence of overt movement (6,9) or even when overt movement is not possible (3,10).…”
mentioning
confidence: 99%
“…This parameter has also varied considerably. For example, Fabiani et al (2004) used 200 msec while Kelley et al (2002) used 1500 msec. Studies that use adaptive algorithms to estimate autoregressive coefficients (e.g., Schlogl et al, 2005) can be regarded as employing an exponential data window.…”
mentioning
confidence: 99%
“…In general the AUCs are in the range of 0.6-0.9 which compares well with analogous 1-dimensional motor imagery BCI paradigms such as (Fabiani et al 2004) which achieves accuracies of between 71.8 and 74.3% or (Ang 2008) which achieves a mean accuracy of 73.3 ± 2.8%.…”
Section: Discussionmentioning
confidence: 60%